INCREASING PRODUCTION WEIGHT OF MODIFIED-BIOSILICA FROM RICE HUSK AND ITS APPLICATIONS AS REINFORCING FILLER IN RUBBER FINISHED GOODS - Kendri Wahyuningsih; Sri Yuliani; Wahyu Diyono; Hoerudin Hoerudin; Tatang Hidayat (Balai Besar Penelitian dan Pengembangan Pascapanen Pertanian, 2021)
Biosilica from rice husks has a potential that can be used as a reinforcing filler in the production of rubber finished goods displace mine silica. But it’s difficult to disperse homogenetically into a rubber finished goods, so it needs to modify the surface using a coupling agent sign. The capacity for the production of modified-biosilica would need to be at a great level to meet the needs of the rubber industry. The purpose of the research is to identify the characteristics of the modified-biosilica by silane TESPT (bis-(3-triethoxysilylpropyl) tetrasulfane) that resulted from increasing the weight of biosilica in the production process and the application as reinforcing filler on the rubber. Increasing of weight in the production process was done gradually on a scale of 0.5; 1; 2; and 5 kg of biosilica per process using a mixer-propeller. The technique on surface modifications was using a one-step modification (OSM) and two-step modification (TSM). Surface modification treatment using TESPT has increased the uniformity of the particle size distribution of the biosilica. Unmodified-biosilica has an average particle size of 717.1 nm (PDI 0.600), while modified-biosilica has an average particle size of 574.6 nm (PDI 0.585). Applications for reinforcing filler in the soles rubber industry are performed in PT Triangkasa Lestari Utama. Research indicates that increasing the weight of biosilica on the surface modifications did not significantly affect the density, lightness, crystallinity, and purity. The applications as reinforcing fillers have increased the quality of rubber finished goods compared with unmodified-biosilica. The best rubber finished goods quality approaching shoes-sol standards is a product that used modified-biosilica by OSM technique. This rubber finished goods has a tensile strength of 5.80 MPa, elongation at break of 425%, tear strength of 23.25% and abrasion resistance of 251.5 mm3 .